(untitled) (Journal of Society of Surgeons of Nepal, 2021)
Zinner syndrome is a rare congenital abnormality of the mesonephric (Wolffian) duct consisting of unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ipsilateral ejaculatory duct obstruction. The syndrome usually presents in the second or third decade of life mainly after the beginning of sexual activity and usually in the form of voiding manifestations. The main imaging modality is magnetic resonance imaging (MRI); however, usually suspected in transabdominal sonography, which may give initial clue to the diagnosis. Herein, we report a rare case of a 24 - year male with right renal agenesis with cystic pelvic mass diagnosed as Zinner syndrome via multimodality imaging.